PROBLEMS OF RELIABILITY OF THE MANIFESTATION OF TECHNICAL AND TACTICAL CAPABILITIES OF WRESTLERS IN CONDITIONS OF COMPETITIVE ACTIVITY (Scientific journal of the Fergana State University, 2024)
AbstractFactors of reliability of the manifestation (use of demonstration) of the technical capabilities of wrestlers at the stages of preparation for responsible competitions. The methodology for evaluating the training of wrestlers. The influence of physical exhaustion (fatigue) of wrestlers on the indicators of technical and tactical capabilities.